Oxygen electroreduction catalysed by laccase wired to gold nanoparticles via the trinuclear copper cluster. Issue 2 (8th November 2016) - Dagys, Marius; Laurynėnas, Audrius; Ratautas, Dalius; Kulys, Juozas; Vidžiūnaitė, Regina; Talaikis, Martynas; Niaura, Gediminas; Marcinkevičienė, Liucija; Meškys, Rolandas; Shleev, Sergey
Abstract : Comparison of conventional and newly developed laccase-based electrocatalytic systems for oxygen reduction. Abstract : Specific wiring of biocatalysts par excellence, viz. redox enzymes, to an electrode can be exploited in the fabrication of high-performance bioelectronic devices. Here we report oxygen electroreduction catalysed by Didymocrea sp. J6 laccase wired to gold nanoparticles via the trinuclear copper cluster. Bypassing the intramolecular electron transfer, which under certain conditions is the rate-limiting step of oxygen bioelectroreduction, has resulted in the fabrication of a high current density biocathode based on high-redox-potential laccase, which is able to operate in electrolytes with a broad pH range in the presence of high fluoride concentrations.